The Relationship between Economic Complexity Index and Export: the Case of Turkey and Central Asian and Turkic Republics - Şeker, Ayberk; Şimdi, Halil (Economy of Regions, 2019)
The paper focuses on the mutual interaction between export from Turkey to Central Asian and Turkic Republics (the CATRs) and exported product range. For measuring the range of exported products, we use economic complexity index (ECI) that refers to the knowledge intensity accumulated in the country’s exported products. In addition, ECI provides information regarding the countries’ export structures and income levels. We explore how export levels of Turkey and the CATRs, which have common religion and ethnicity, and the countries’ ECI scores interact with each other. In this regard, we demonstrate how export affects the countries’ ECI for both the CATRs and Turkey. For this purpose, we study the possible relationship between mutual trade volume and the countries’ ECI scores by employing Westerlund’s cointegration analysis, Pooled Mean Group Estimator (PMGE) model and Dumitrescu-Hurlin’s panel causality method. We used the data on the researched countries for the period from 1996 to 2015 collected from official web sites. We have found that export from Turkey to the CATRs and Turkey’s ECI scores have a long-term relationship. Additionally, there is a unidirectional causality relationship from Turkey’s export to the CATRs to Turkey’s ECI score and from the CATRs’ ECI scores to the CATRs’ export to Turkey. To sum up, our findings support the hypothesis that higher trade volume between Turkey and the CATRs increases the export of complex products for both sides. Based on the results, stronger mutual trade relations increase the total gain not only for Turkey but for the CATRs, too. Lastly, in future studies, we plan to cover all Post-Soviet countries and reveal the relations between bilateral trade and the range of exported products.